Does perthionitrite (SSNO(-)) account for sustained bioactivity of NO? A (bio)chemical characterization. - Wedmann, Rudolf; Zahl, Achim; Shubina, Tatyana; Dürr, Maximilian; Heinemann, Frank Wilhelm; Bugenhagen, Bernhard Eberhard Christian; Burger, Peter; Ivanovic-Burmazovic, Ivana; Filipovic, Milos (Inorganic Chemistry, 2015)
Hydrogen sulfide (H2S) and nitric oxide (NO) are important signaling molecules that regulate several physiological functions. Understanding the chemistry behind their interplay is important for explaining these functions. The reaction of H2S with S-nitrosothiols to form the smallest S-nitrosothiol, thionitrous acid (HSNO), is one example of physiologically relevant cross-talk between H2S and nitrogen species. Perthionitrite (SSNO(-)) has recently been considered as an important biological source of NO that is far more stable and longer living than HSNO. In order to experimentally address this issue here, we prepared SSNO(-) by two different approaches, which lead to two distinct species: SSNO(-) and dithionitric acid [HON(S)S/HSN(O)S]. (H)S2NO species and their reactivity were studied by (15)N NMR, IR, electron paramagnetic resonance and high-resolution electrospray ionization time-of-flight mass spectrometry, as well as by X-ray structure analysis and cyclic voltammetry. The obtained results pointed toward the inherent instability of SSNO(-) in water solutions. SSNO(-) decomposed readily in the presence of light, water, or acid, with concomitant formation of elemental sulfur and HNO. Furthermore, SSNO(-) reacted with H2S to generate HSNO. Computational studies on (H)SSNO provided additional explanations for its instability. Thus, on the basis of our data, it seems to be less probable that SSNO(-) can serve as a signaling molecule and biological source of NO. SSNO(-) salts could, however, be used as fast generators of HNO in water solutions.

Improved tag-switch method reveals that thioredoxin acts as depersulfidase and controls the intracellular levels of protein persulfidation - Wedmann, Rudolf; Onderka, Constantin; Wei, Shengwei; Szijarto, Istvan Andras; Miljkovic, Jan; Mitrovic, Aleksandra; Lange, Mike; Savitsky, Sergey; Yadav, Pramod Kumar; Torregrossa, Roberta; Harrer, Ellen G.; Harrer, Thomas; et al. (Chemical Science, 2016)
Hydrogen sulfide (H2S) has emerged as a signalling molecule capable of regulating several important physiological functions such as blood pressure, neurotransmission and inflammation. The mechanisms behind these effects are still largely elusive and oxidative posttranslational modification of cysteine residues (protein persulfidation or S-sulfhydration) has been proposed as the main pathway for H2S-induced biological and pharmacological effects. As a signalling mechanism, persulfidation has to be controlled. Using an improved tag-switch assay for persulfide detection we show here that protein persulfide levels are controlled by the thioredoxin system. Recombinant thioredoxin showed an almost 10-fold higher reactivity towards cysteine persulfide than towards cystine and readily cleaved protein persulfides as well. This reaction resulted in H2S release suggesting that thioredoxin could be an important regulator of H2S levels from persulfide pools. Inhibition of the thioredoxin system caused an increase in intracellular persulfides, highlighting thioredoxin as a major protein depersulfidase that controls H2S signalling. Finally, using plasma from HIV-1 patients that have higher circulatory levels of thioredoxin, we could prove depersulfidase role in vivo.
EVALuna2:13290

Nitrosopersulfide (SSNO−) decomposes in the presence of sulfide, cyanide or glutathione to give HSNO/SNO−: Consequences for the assumed role in cell signalling - Ivanovic-Burmazovic, Ivana; Wedmann, Rudolf; Filipovic, Milos (Interface Focus, 2017)
Keywords: Nitric oxide; Hydrogen sulfide; Thionitrous acid; Nitrosopersulfide

Working with "H2S": Facts and apparent artifacts - Wedmann, Rudolf; Bertlein, Sarah; Macinkovic, Igor; Böltz, Sebastian; Miljkovic, Jan; Munoz Becerra, Luis; Herrmann, Martin; Filipovic, Milos (Nitric Oxide-Biology and Chemistry, 2014)
Hydrogen sulfide (H2S) is an important signaling molecule with physiological endpoints similar to those of nitric oxide (NO). Growing interest in its physiological roles and pharmacological potential has led to large sets of contradictory data. The principle cause of these discrepancies can be the common neglect of some of the basic H2S chemistry. This study investigates how the experimental outcome when working with H2S depends on its source and dose and the methodology employed. We show that commercially available NaHS should be avoided and that traces of metal ions should be removed because these can reduce intramolecular disulfides and change protein structure. Furthermore, high H2S concentrations may lead to a complete inhibition of cell respiration, mitochondrial membrane potential depolarization and superoxide generation, which should be considered when discussing the biological effects observed upon treatment with high concentrations of H2S. In addition, we provide chemical evidence that H2S can directly react with superoxide. H2S is also capable of reducing cytochrome c(3+) with the concomitant formation of superoxide. H2S does not directly react with nitrite but with NO electrodes that detect H2S. In addition, H2S interferes with the Griess reaction and should therefore be removed from the solution by Cd(2+) or Zn(2+) precipitation prior to nitrite quantification. 2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO) is reduced by H2S, and its use should be avoided in combination with H2S. All these constraints must be taken into account when working with H2S to ensure valid data.
EVALuna2:12902